Kesejahteraan Keluarga: Pernikahan Lintas Organisasi Keagamaan - Mirza Elmy Safira; Nelud Darajaatul Aliyah; Didit Darmawan; Wakid Evendi; Muhammad Zakki (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
Marriages across religious organizations reflect the complexity of social and cultural dynamics in contemporary society. This article examines the challenges and adaptation strategies of couples in such marriages. With a focus on understanding, compromise, social support and family identity, the research highlights the central role of society and religious communities to shape family well-being. The analysis also shows that acceptance of religious differences, open communication and constructive conflict management are key aspects to building healthy relationships. The results of this study provide valuable insights for couples across religious organizations, family guidance practitioners, and religious community leaders to understand the dynamics of such marriages and strengthen efforts to support family well-being within the framework of religious diversity.